Patients Given Take Home Medications Instead of Paper Prescriptions Are More Likely to Return to Emergency Department. Issue 6 (June 2017) - Sarangarm, Dusadee; Sarangarm, Preeyaporn; Fleegler, Melissa; Ernst, Amy; Weiss, Steven
Objective: The aim of this study was to compare the 30-day emergency department (ED) return rate between patients given a Take Home Medication pack (THM) versus a standard paper prescription (SPP) prior to discharge.Methods: This was an observational, prospective cohort study in an urban, university-affiliated, level I trauma center. Patients were identified through daily pharmacy reports. Consecutive adult patients discharged from the ED with either a THM or equivalent SPP were included. For each patient, baseline characteristics including age, gender, primary care provider (PCP), primary language, ethnicity, marital status, and insurance status were recorded from the electronic medical record (EMR). Review of the EMR was used to determine whether patients returned to the ED within 30 days and whether the return visit was for all-causes or for the same complaint targeted by the THM or SPP from the index visit. Similarly, visits to other providers in the health system within 30 days were recorded.Results: A total of 711 patients were included in the study, with 268 receiving a THM and 443 receiving a SPP. In comparison with the SPP group, the THM group was more likely to have an all-cause return (Relative Risk [RR] = 1.7, P < .01). Variables associated with increased odds of returning to the ED within 30 days included study group (adjusted Odds Ratio [aOR]: 1.7), male gender (aOR: 1.6), African American ethnicity (aOR: 3.0), public insurance (aOR: 3.3), and institutional financial assistance (aOR: 5.0). The difference between study groups for index visit complaint-specific returns was not significant.Conclusions: Patients receiving a THM demonstrated a higher all-cause return rate than patients receiving a SPP. A randomized study is needed evaluating the effect of THM on return ED visits.